Celso Furtado: man, work and path - Silveira, Jorge Luis Rocha da (2024)
The main objective of this essay is to honor – albeit briefly and belatedly – the economist and writer Celso Furtado. To this end, a gathering of his biography and performance in the Superintendence of Development of the Northeast (SUDENE) was made. Based on these points, information was selected on his personal background and social concern, which is believed to be revealed in the presence of the aforementioned state agency, in other actions, and also in much of his production. In addition, it was intended to recall the main events that marked the honoree’s trajectory. It is hoped, thus, that Furtado's history will help to identify his role in the national debate that led to the inclusion of the theme of poverty and development in the governance agenda, from the year 1950 onwards.